7 - Somali Language and Oral Tradition in Post-conflict Life in the US: What Does the Future Hold? - Sarah Drake; Eddah Mutua-Kombo (Africa Media Review, 2009)
As global conflicts increasingly force people to leave their homelands, it is important we become aware of the issues that impact on different aspects of refugees’ lives in foreign lands. A variety of problems are associated with forced migration, notably challenges of cultural adaptation such as language issues, cultural assimilation, cultural adaptation, identity, loss of social networks of relatives, friends and neighbours, harsh climates, racism and so on. This article discusses some of the concerns expressed by Somali refugees living in Mid- West United States of America. They fear that the Somali language and oral traditions might be lost if attempts are not made to preserve them. Specifically, the authors examine the efforts to and challenges of preserving the language and oral traditions in a post-conflict setting. The article concludes by pointing to a question about the future of third generation Somali-Americans who have adapted the English language and see no economic and social benefits in the Somali language for them.